Pemberdayaan Siswa Dalam Peningkatan Pengetahuan PHBS Dengan Tuberkulosis Pada Anak Sekolah Dasar Di Desa Oelomin Kecamatan Nekamese Kabupaten Kupang Tahun 2023 - I Gede Putu Arnawa; Ni Made Susilawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Clean and healthy living behavior (PHBS) is a reflection of a person's lifestyle who always pays attention to and maintains their health. Pulmonary TB is an inflammatory disease of the lung parenchyma due to infection with the Mycobacterium tuberculosis bacteria. Schools have the potential to increase the incidence of pulmonary TB if students do not maintain personal and environmental hygiene. The aim of this community service is to educate students about clean and healthy living behavior for elementary school students, especially preventing TB transmission in Oelomin Village, Nekamese District, Kupang Regency. The activity was carried out at SDN 2 Tunfeu, Oelomin Village, where students from grades 1 to 6 were educated about preventing TB disease, how the disease is transmitted, how to behave in a clean and healthy lifestyle to avoid tuberculosis. Before the activity took place, students were given a questionnaire about tuberculosis to determine the level of student knowledge. Then practice the behavior of washing hands with soap at school. At the end of this activity, students were asked questions about preventing tuberculosis and how to wash their hands properly. After the activity is finished, students are given another questionnaire to measure student understanding. The results of this activity show that the percentage of students who are not good at carrying out PHBS practices for preventing pulmonary TB is more often found in the group with the poor knowledge category (52%) compared to the group with the good knowledge category (20%). Students' lack of knowledge about pulmonary TB and PHBS is that 75% of students do not know the symptoms of pulmonary TB, namely coughing for more than 3 weeks. As many as 66.5% of students did not know the cause of pulmonary TB, namely Mycobacterium tuberculosis infection. As many as 40% of respondents did not know about the transmission of pulmonary TB disease when sufferers sneezed and 54% did not know about the transmission of pulmonary TB disease when sufferers spoke. As an outcome of this activity, it is hoped that students will be able to implement clean and healthy living habits at home, as well as using masks when they are sick to prevent tuberculosis.